ASSESSMENT OF THE RELATIONSHIP BETWEEN CORPORATE SOCIAL RESPONSIBILITY ENVIRONMENTAL GOALS IMPLEMENTATION AND FINANCIAL AND OPERATIONAL INDICATORS OF AIRLINES - Lidiia SAVCHENKO; Oksana OVDIIENKO; Mykola BOICHENKO; Tetiana MOSTENSKA (Scientific Journal of Silesian University of Technology. Series Transport)
The main idea of the article is assessing the feasibility of introducing Corporate Social Responsibility (CSR) for airlines. Moreover, the authors think that the environmental aspect in CSR is the most important, which predetermined the focus on this CSR component in the article. The article provides several examples of airlines that actively use CSR to improve their image, attract new, and increase the loyalty of existing customers. Environment indicators of the flight operations group on the performance indicators were established.